Parasitylenchus sp. (Tylenchomorpha: Allantonematidae) parasitizing field populations of Harmonia axyridis (Coleoptera: Coccinellidae) - Susanne HARDING (European Journal of Entomology, 2011)
Adults of the invasive harlequin ladybird, Harmonia axyridis (Coleoptera: Coccinellidae), were found to be parasitized by nematodes (Tylenchomorpha: Allantonematidae) in Denmark. The nematodes were identified as Parasitylenchus sp. Major morphological characters of the nematodes did not differ significantly from Parasitylenchus coccinellinae Iperti & van Waerebeke 1968, but minor deviations in egg dimension and tail length were measured. Parasitism was only recorded in early autumn, with prevalence ranging from 2 to 33%. Adult and juvenile nematodes occurred together in the body cavity of both female and male H. axyridis.